Responses of Nitrogen Metabolism, Uptake and Translocation of Maize to Waterlogging at Different Growth Stages - Ren, Baizhao; Dong, Shuting; Zhao, Bin; Liu, Peng; Zhang, Jiwang (Frontiers in Plant Science, 2017)
We performed a field experiment using the maize hybrids DengHai605 (DH605) and ZhengDan958 (ZD958) to study nitrogen uptake and translocation, key enzyme activities of nitrogen metabolism in response to waterlogging at the third leaf stage (V3), the sixth leaf stage (V6), and the 10th day after the tasseling stage (10VT). Results showed that N accumulation amount was significantly reduced after waterlogging, most greatly in the V3 waterlogging treatment (V3-W), with decreases of 41% and 37% in DH605 and ZD958, respectively. N accumulation in each organ and N allocation proportions in grains decreased significantly after waterlogging, whereas N allocation proportions increased in stem and leaf. The reduction in stem and leaf N accumulation after waterlogging was mainly caused by a decrease in dry matter accumulation, and a reduction in N translocation from stems and leaves to grains after waterlogging. Additionally, waterlogging decreased the activity of key N metabolism enzymes (nitrate reductase, glutamine, glutamate synthase, and glutamate dehydrogenase), and the most significant reduction in V3-W with a decrease of 59, 46, 35, and 26% for DH605, and 60, 53, 31, and 25 for ZD958, respectively. Waterlogging disrupted N metabolism, hindered N absorption and transportation, and decreased maize yield.